A study on workability and mechanical properties of eco-sustainable self-compacting concrete incorporating PCB waste and fly ash. (20th December 2021) - Sua-iam, Gritsada; Chatveera, Burachat
Abstract: Electronic wastes containing metallic and nonmetallic hazardous materials, if left untreated, are severely harmful to the environment, social, ecosystem, and human well-being. In this study, the effects of substituting recycled electronic waste, i.e., printed circuit board (PCB) dust, and fly ash (FA) concurrently as a partial replacement of ordinary Portland cement (OPC) in self-compacting concrete (SCC) was investigated to explore a novel electronic waste recycling method and new material of construction. The decisive parameters of e-waste mixed cement SCC are workability characteristics and hardened properties. According to the design of experiments, the ratio of PCB dust waste in OPC were 0%, 5%, 10%, 15%, 20%, and 30% whilst the ratio of FA in OPC were 10%, 20%, and 30% by volume. Workability characteristics were verified by means of rheological behaviors, i.e., slump diameter, T500 flow time, test V-funnel test, J-Ring test and L-box test. Compressive strength, split tensile strength, flexural strength, and ultrasonic pulse velocity up to 180 days were determined for its hardened properties. According to the result, recycled PCB dust with FA can be used as cement replacement for SCC. Combining use of recycled PCB dust and FA as filler and pozzolanic synergistically yielded satisfactory results, e.g., greater than 60 MPa of compressive strength at 28 days for 5% PCB dust and 10% FA. In addition, compressive strength at 180 days of highest cement replacement level at 60% was greater than 40 MPa. Eventually, there are opportunities to use combined PCB dust and FA as cement replacement in SCC which yields cost saving and eco-sustainable SCC products that are economically and environmentally beneficial for the construction industry.